Halal Product Standardization and Digital Marketing Mentorship for Muslimah Community in Southern Thailand - Marini Soraya (Future Tecno-Science Publisher, 2025)
This article reports on a community service program (Pengabdian kepada Masyarakat) conducted in Pattani and Narathiwat, Southern Thailand, in collaboration with Fatoni University, targeting Muslimah entrepreneurs and home-based food producers. The program addressed two critical gaps in the local small business ecosystem: the absence of systematic understanding of halal product certification and labeling standards, and limited capacity in digital marketing. Through a series of structured workshops, practical mentoring sessions, and hands-on training activities conducted across 2024, a total of 48 women entrepreneurs participated in learning activities covering halal product standardization, brand identity development, and social media marketing through platforms such as TikTok, Instagram, and Facebook. Pre- and post-program assessments demonstrated a measurable increase in participants' comprehension of halal certification procedures, with 78% of participants reporting improved confidence in marketing their products digitally. Several participants successfully redesigned product packaging to comply with halal labeling guidelines and launched active social media business accounts during the program period. This article discusses the program methodology, outcomes, challenges encountered, and recommendations for scaling similar initiatives across Muslim-majority communities in the region.